Innovative Time Management Strategies and Improved Academic Staff Performance in Nigerian Public Universities in South West, Nigeria - Owolabi, Oluwapelumi Bunmi; Adetayo, Hezekiah Olufemi; Adegoke, Omofolasaye Omobolanle (African Journal of Stability and Development (AJSD), 2025)
The contribution of lecturers in public tertiary institutions in south west, Nigeria, to national development remains underexplored, while their performance is hindered by institutional inefficiencies and overwhelming workloads. This study, therefore, investigates the direct effect of innovative time management strategies on the performance of academic staff in the Nigerian public universities in south west, Nigeria; assesses work engagement as a mediator in the relationship between time management and performance of academic staff; and evaluates the extent to which reduced role overload mediate in the relationship between time management and performance of academic staff in Nigerian public Universities in south west, Nigeria. The research is anchored on the Resource-Based Theory and the Job Demand Resource Model. This study was conducted quantitatively with a cross-sectional survey used to collect data from 350 academics from 6 public universities in south west, Nigeria. Findings from the study indicated that innovative time management strategies substantially improved academic staff performance (β=0.53, p < .001). The results also showed, albeit marginally, work engagement and role overload as moderating variables. The study states that the use of modern techniques, such as digital batching, time management systems, and the use of a modern prioritisation matrix improved the performance of employees through increased engagement in deep work and decongestion of role overload. The engagement outlined in the paper is unique as it describes the applicability of the integration of organisational psychology to the theory and practice of management within the university system.